Exercising Arctic Institute Citizenship - Robinson, Mike (ARCTIC, 1997)
In this Arctic we return to a trusted format that harkens back to the first issues of the journal in the late 1940s. We are once again combining news of Arctic Institute members, essay format contributions on topics of immediate interest to our readers, and yes, even a cartoon, with the usual Arctic staples of peer-reviewed papers, book reviews, and the occasional Arctic profile. In this manner the entire message of the institute can find a safe harbour in one publication, and over time Arctic will demonstrate a broader appeal, especially to those members whose love of things northern is less scientific than topical, familial and geographic. We want all of our members to find pleasure in their affiliation through reading Arctic. .